Couples violence among teenagers students from public high schools of North Lima - Gonzalez-Cordero, Cristian N. (2020)
Objective: Determine the frequency of partner violence among teenager students of state high schools in a district of North Lima. Materials and methods: Cross-sectional descriptive study conducted in five state high schools at Puente Piedra district. The instrument used was the Conflict Questionnaire in teenager relationships (CQTR). Results: Of the 208 teenagers (Mean = 15.48, SD = 0.99, Range: 14 to 18), 59.6% (n = 124) corresponded to the male sex and the female, most of them were from the third and fourth year. Almost all the teenagers have committed or suffered some type of violence; emotional verbal violence was the most frequent in both groups. The violence committed, in its relational violence dimension, occurred in a greater proportion in male teenagers [p = 0.045; OR = 2.52 (95% CI: 1.01-6.33)]. Violence committed in the threat dimension also occurred in a greater proportion in males [p = 0.002; OR = 8.15 (95% CI: 1.71-38.87)]. The violence suffered, in the verbal emotional dimension, threat and physical violence was presented in greater proportion in male teenagers, whit significant differences in verbal violence [p = 0.04; OR = 2.45 (1.99-3.02)], threat [p = 0.001; OR = 14.55 (95% CI: 1.78-118.58)] and in physical violence [p = 0.009; OR = 4.46 (95% CI: 1.34-14.86)]. Conclusion: The violence committed and suffered in teenager couples is frequent and occurs mainly in males, the emotional verbal component and the threat predominated. It is recommended to strengthen the work of both the education and health sector to contribute to the reduction of violence.